The Role of The Young Generation In Stunting Prevention To Create Superior Human Resources In Abang Village, Abang District, Karangasem Regency - Marhaeni, A.A.I.N; Nyoman Yuliarmi, Ni; Jati Primajana, Dewa; Pradnyadewi, Diah; Ketut Sudibia, I; Kadek Eka Jayanthi, Ni; Sinthya Aryasthini M, Made; Nyoman Reni Suasih, Ni; Santana Putra A, Made (CV. Inara, 2023)
Addressing and reducing the prevalence of stunting in Indonesia, supported by the reduction of stunting in various regions throughout the country, is a highly relevant program in achieving Indonesia's vision for 2045 as declared by the President of the Republic of Indonesia. In realizing this vision, the program to reduce the prevalence of stunting in Indonesia becomes highly relevant to achieve this overarching goal. Therefore, all elements of society, in accordance with their respective roles, can contribute to supporting the realization of Indonesia's advanced vision. Hence, studies regarding the condition of stunting in its various dimensions become very important and relevant. The purpose of this Community Engagement activity is to: 1) Analyze the knowledge, attitudes, and practices of young generations in stunting prevention in a rural village; 2) Enhance the role of young generations in stunting prevention in their village. The Community Engagement activity was conducted in Abang Village, Karangasem Regency. This regency was chosen because it has the highest prevalence of stunting among the regencies in Bali Province. The activity involved young people in the village, known as